About subspecies affinity of the Crimean red-backed shrike, Lanius collurio (Passeriformes, Laniidae) - Tajkova, S.U.; Red’kin, Y.A. (Збірник праць Зоологічного музею, 2013)
The conducted comparative morphological analysis (in particular comparative measurements of adult birds and coloration of adult males) allow distinguishing of the Crimean endemic subspecies Lanius collurio tauricus Moltschanov, 1917 from the widespread L. c. collurio. L. c. tauricus is characterized by the smaller size and narrower (in average) brown mantle of adult males, if compared to L. c. collurio. It also differs by shorter wings and bills from the subspecies L. c. kobylini, which is widespread in the Caucasus and Asia Minor. Also, from both these subspecies L. c. tauricus is distinguishable by the wider base of the bill. Вивчення розмірних ознак дорослих птахів та забарвлення дорослих самців дозволило визначити особливості кримського ендемічного підвиду, Lanius collurio tauricus Moltschanov, 1917. Від широко розповсюдженого L. c. collurio він відрізняється дрібними розмірами і в середньому більш вузькою коричневою мантією у дорослих самців. Від кавказько-малоазійського підвиду, L. c. kobylini, кримська форма відрізняється коротшими крилами та дзьобом. Від обох згаданих підвидів L. c. tauricus добре відрізняється ширшою основою дзьоба. Изучение размерных признаков взрослых птиц и окраски взрослых самцов позволило найти особенности крымского эндемичного подвида, Lanius collurio tauricus Moltschanov, 1917. От широко распространенного L. c. collurio он отличается мелкими размерами и в среднем более узкой коричневой мантией у взрослых самцов. От кавказско-малоазиатского подвида, L. c. kobylini крымская форма отличается более коротким крылом и клювом. От обоих упомянутых подвидов L. c. tauricus хорошо отличается более широким основанием клюва. The authors express their sincere thanks to Vladimir M. Loskot (ZISP), Aleksandr M. Peklo, Anna V. Klochko (NMNH), Pavel S. Tomkovich (ZMSU), Tatyana M. Devyatko (MNKHNU), Igor V. Fadeev (SDM) and Nikolay F. Veselsky (ZRM) for the assistance during the work with collections of their institutions.